Dynamic accumulation of a high-grade gas hydrate system: insights from the trial production gas hydrate reservoir in the Shenhu area, northern South China Sea - Zhang, Wei; Liang, Jinqiang; Su, Pibo; Meng, Miaomiao; Huang, Wei; Liu, Pengqi; Yuan, Sheng; Ji, Chunsheng (Frontiers in Marine Science, 2024)
The ultimate enrichment level and quantity of gas hydrate resources are influenced by the dynamic process of accumulation and preservation. High-resolution 3-D seismic data, logging while drilling (LWD), pressured coring, and in situ testing were used to characterize the dynamic accumulation and preservation of the trial production high-grade gas hydrate reservoir (HGGHR) in the Shenhu area. Through seismic variance analysis and ant-tracking, we found that newly identified mud diapir-associated faults with three development stages controlled the migration and accumulation of gas hydrate and shifted the base of the gas hydrate stability zone (BGHSZ), resulting in dynamic accumulation and dissociation of gas hydrates. The recognized double bottom simulating reflectors (BSRs) were concluded to have been formed due to the shift of the BGHSZ caused by the variational equilibrium conditions. The interval between the double BSRs was inferred to be a disequilibrium zone where gas recycling occurred, contributing to the coexistence of gas hydrates and free gas and the dynamic formation of the HGGHR. Multiple gliding faults formed within the GHSZ in the late period have altered the HGGHR and control the present thickness and distribution of the gas hydrates and free gas in the hanging wall and footwall.Under the influence of geothermal fluids and the fault system associated with the mud diapir, the trial production of the HGGHR experienced dynamic accumulation with three stages, including early accumulation, medium-term adjustment, and late alteration and preservation. We conclude that threefour factors affected the formation, distribution, and occurrence of the HGGHR: the geothermal fluids accompanying the deep mud diapir below the reservoir, the dual supply of thermogenic gas and biogenic gas, the recycling of hydrate gas beneath the BGHSZ, and the post-gas hydrate faults developed within the GHSZ. A geological model illustrating the dynamic formation of the trial production HGGHR was proposed, providing a reference for future 3 exploration of HGGHRs with a good great production potential in deepwater settings.